Manufacturing technology : metal cutting and machine tools / P N Rao - Rao, P. N. (Posinasetti Nageswara), 1947-
This text offers a comprehensive treatment of conventional and emerging technologies in manufacturing engineering and production process. Lucid presentation, expanded topical coverage and rich pedagogy make this an excellent book for students, teachers and practicing engineers.